(3QSGdI aj aVd LOI (B/s - (3GHf agO, eMeO Hf YHO GdYRjR Hf YeQs 891-954 (3gLQjs; (3YeQ, Ydjs; (3GHf agO, eMeO Hf YHO GdYRjR Hf YeQ,s 891-954 (3gLQj(B.s ((3GdbGgQI (B:s (3TQcI fhGHZ GdacQ ddfTQ hGdJhRjY hGdJUOjQ,s, 2010)
(3jJfGhd GdcJGH aVd eOjfI LOI hCgejJgG GdJGQjNjI hGdOjfjI, GdcJGH jJVef eYdheGJ Yf JGQjN GdeOjfI, hCHQR GdCMOGK GdJj eQJ HgG, HGdEVGaI Edi PcQ HYV GdTNUjGJ GdHGQRI GdJj YGTJ ajgG, eOjfI LOI dgG JGQjN Whjd jeJO Edi MhGdj (B3000 (3SfI, aj GdHOGjI cGfJ eSJhWfI UZjQI ddUjGOjf GdPjf GSJbQhG ajgG HYO QMdGJ GdUjO YHQ GdHMQ GdCMeQ, haj YgO GdNdjaI GdQGTOj YKeGf Hf YaGf, MOK JMhd cHjQ aj JGQjN LOI YfOeG CeQ HJMhjdgG Edi ejfGA dGSJbHGd MLGL GdHMQ GdeJLgjf dCOGA GdML aj ecI GdecQeI YGe (B647(3e, LOI cGfJ eYQhaI YfO GdYQH bHd GdESdGe, hcGfJ ejfGA gGeG decI GdecQeI(B. (3aj GdYUhQ GdhSWi, CUHMJ LOI eQcRG JLGQjG QFjSjG HSHH ehbYgG GdGSJQGJjLj Ydi GdHMQ GdCMeQ, eeG LYdgG HhGHI ddMLGL hGdJLGQ GdbGOejf ef eNJda CfMGA GdYGde GdESdGej(B. s
(3cTGa (B: (3UaMI (B26.s
(3HHdjhLQGajI (B: (3UaMI (B27-28.s
Keywords: (3LOI (B((3GdSYhOjI(B)s -- (3aVGFds -- (3JGQjNs